3D-cathode design with foam-like aluminum current collector for high energy density lithium-ion batteries. (April 2018) - Fritsch, M.; Standke, G.; Heubner, C.; Langklotz, U.; Michaelis, A.
Highlights: NCM cathodes with 3D aluminum foam collector for high energy lithium-ion batteries. LiNi1/3 Mn1/3 Co1/3 O2 cathodes with high active material loading up to 42 mg cm −2 . Area specific capacities of up to 7 mAh cm −2 (0.2C) and 2.3 mAh cm −2 (2.0C). Good cycle life and rate capability performance of 3D NCM foam electrodes. Process enables design freedom to adjust trade-off between energy and power density. Abstract: Increasing the area specific capacity and reducing the inactive/active material ratio of cathodes and anodes is considered to be a promising approach to improve the energy density of lithium-ion batteries. In principle, this can be achieved by increasing the thickness and the active material mass loading of the electrodes. However, the fabrication of thick electrodes with good electrochemical performance is challenging regarding the drying process, mechanical stability, electronic conductivity, etc. The application of Al-foams as current collector provides a 3D electronic conductive network, which can host high loadings of active material combined with high mechanical stability. Herein, we demonstrate a slurry infiltration process capable to fabricate cathodes with high active material loading. A variety of LiNi1/3 Mn1/3 Co1/3 O2 (NMC111) based cathodes with thicknesses up to 260 μm and area specific capacities high as 7 mAh cm −2 are investigated comprehensively. The electrodes exhibit good cycle life and rate capability performance due to the unique 3D current collector concept. Even at the 2.0C discharge rate, an area specific capacity of 2.3 mAh cm −2 is obtained, which is high in comparison to conventional Al-foil concepts. The design freedom of the presented approach is illustrated by the fabrication of cathodes optimized for high rate capability.